Advances in Biosensor Technology: Innovation to the Future - อเนกเวียง, ปนัดนา; ภัทรมานนท์, รินา (KKU Science Journal, 2013)
Development of diagnostic technique called biosensor is currently of great interest for researchers and inventors for their many advantages. Using laboratory instruments like GC, HPLC, microsphere-based arrays, RIA, and ELISA for diagnostics has limitations in terms of time, cost, several steps, and hazardous chemicals. In addition, although current diagnostic test kits like pregnancy test kit are available and very easy to use, it is only a qualitative determination. Diagnosis of other biomarkers or chemicals sometimes requires a quantitative means to differentiate the quantity even in trace amount, or to indicate early stage of the diseases. For examples, fetoprotein is a biomarker of hepatocellular carcinomas in serum and carcinoembryonic antigen of carcinoembryonic. Research and development in biosensors or small diagnostic test kit with high sensitivity have been continually improved. Those consist of the invention of a portable analysis device for test strip quantities, electrochemical sensors, labon-a-chip, lab-on-a-paper and mobile application. It might in the future replace the traditional instruments due to reduced cost, easy-to-use, and knowing the result within minutes. In addition, the detectors for biosensor are usually small so it’s ideal for point-of-care or point-ofsite purpose. However, the current stat-of-the-art instruments are nevertheless essentials since they are able to detect wide-ranges of biomarkers. We believe that once biosensors are developed for more markers as comparable to the traditional tools, it will bring exceedingly advanced benefit in disease diagnostics.